KONSERVASI DAN PEMANFAATAN SUMBER DAYA GENETIK KACANG HIJAU - Lukman Hakim (Jurnal Penelitian dan Pengembangan Pertanian, 2008)
Conservation and utilization of mungbean genetic resourcesCurrently 1,024 mungbean germplasm accessions consisted of 142 local and 833 introduced varieties, 32 promising lines, and 17 commercial varieties are being maintained in the National Genebank at Indonesian Center for Agricultural Biotechnology and Genetic Resources Research and Development. The seeds of mungbean germplasm are preserved in two types of invironment. The active collections are maintained at 15–18 C as short-term storage, while the base collections are kept at -5 C as mid-term storage. A wide range of variability was observed for all the agronomic characters studied, especially for days to maturity, plant height, pods per plant, and seed size. Germplasm evaluation has identified several resistance sources. One accession ( V4281 ) was resistant to beanflies, three accessions were resistant to cercospora leaf spot, and six accessions were resistant to powdery mildew. The variation for protein content of germplasm was not very broad. Two accessions ( VR290 and VR194 ) had the highest protein content of 30%, respectively. Germplasm evaluation also obtained four accessions which had largest seed size and good seed quality. Utilization of mungbean genetic resources has made a significant contribution on mungbean breeding program. Several accessions had been officially released as new cultivars, and a number of accessions have been used as sources of resistance on hybridization program. Currently 19 commercial mungbean varieties have been officially released in the country. oKeywords: Mungbean, genetic resources, conservation, utilization